Educational Choice, Initial Wage and Wage Growth - Jacopo Mazza; Hans van Ophem (Tinbergen Institute, 2020)
We investigate the major choice of college graduates where we make choice dependent on expected initial wages and expected wage growth per major. We build a model that allows us to estimate these factors semiparametrically and that corrects for selection bias. We estimate the model on the combined NLSY79 and NLSY97 samples. We find markedly different results in expected real wage growth and expected initial wages across majors. Furthermore, the dierences in these expectations appear to be relevant for major choice.
Keywords: J31; C14; C34; D81; 330; Wage inequality; Wage uncertainty; Unobserved heterogeneity; Selection bias; Decision-making under Risk and Uncertainty; Semiparametric estimation